PENGARUH CORPORATE GOVERNANCE EFFICIENCY TERHADAP PENGUNGKAPAN SUSTAINABILITY REPORT DAN DAMPAKNYA TERHADAP KINERJA KEUANGAN - Ainaya Al Fatihah; Jacobus Widiatmoko (Faculty of Economics and Business, Universitas Warmadewa, 2022)
Disclosure of sustainability reports for companies is a form of responsibility to stakeholders related to the company's economic, environmental and social performance. The company will get recognition from stakeholders and be recognized by the wider community as a company that has carried out its social and environmental obligations. With the disclosure of the sustainability report, the company will gain the trust of stakeholders, both investors and customers, so that the company's productivity and sales will increase and company profits will increase. Disclosure of the sustainability report on the company will have an impact on the company's financial performance. This study aims to examine the effect of corporate governance efficiency on sustainability report disclosure and its impact on financial performance. The population of this study are manufacturing companies listed on the Indonesia Stock Exchange (IDX) in 2018-2020. The population obtained is 536 with a sample of 427 companies using purposive sampling method. The analysis technique uses multiple linear regression analysis. The results of the study prove that corporate governance efficiency has a positive effect on the disclosure of the sustainability report. Disclosure of sustainability reports has a positive effect on financial performance. Further research development can use variables outside of research that theoretically affect the disclosure of sustainability reports and financial performance, such as managerial ownership and institutional ownership.